A real-time aging monitoring method of parallel-connected IGBT modules. (15th March 2021) - Yuan, Weibo; He, Yigang; Li, Zhigang; Ruan, Yi; Lu, Li; Li, Bing
Abstract: A parallel connection of electronic devices in the energy system is currently the only and the most effective way to expand the power capacity. For a circuit containing loads, a minor change of the conduction resistance of electronic devices is not suitable for measurement, but for each parallel branch, its change will be more obvious through current distribution. In this paper, we proposed a current-based method for condition monitoring of the aging process of the electronic modules. The aging information on the package is analyzed and calculated to quantifiable convert to its conduction resistance and then to the current distribution of each branch. By detecting and comparing the value of the current, the aging process can be monitored in real-time. The proposed method has the advantages of low cost and easy implementation. More in detail, it does not need for multi-point monitoring of case temperature, or complicated circuit design for minor changes in voltage monitoring. Finally, the accuracy of the proposed method is validated by simulations and experimental results show a good agreement. Index Terms: IGBT, Condition monitoring, Aging process, Parallel connection.